EVALUASI PROGRAM PERTUKARAN MAHASISWA MERDEKA DALAM MENINGKATKAN ORIENTASI KEBHINEKAAN MAHASISWA UNIVERSITAS NUSA CENDANA KUPANG - Ansiana Gele Wae; Larensius P. Sayrani; Jim Briand Kolianan (Journal Education and Government Wiyata, 2025)
This research was conducted to analyze and describe the evaluation of the Independent Student Exchange program in increasing the diversity orientation of students at Nusa Cendana University, Kupang. This research uses a descriptive qualitative approach, to provide a precise description and explanation of the conditions or symptoms encountered. In this research, the author uses the evaluation theory proposed by William N. Dunn (2003) in program evaluation using 2 evaluation indicators, namely effectiveness and accuracy. The research results show that the Independent Student Exchange program has shown positive results in increasing the diversity orientation of Nusa Cendana University students. This can be seen from its effectiveness, this program has succeeded in transforming students' understanding from theoretical to based on direct experience, forming characters who are more tolerant of diversity, and providing comprehensive learning through the Nusantara Module activities. In terms of accuracy, the program shows conformity with the Ministry of Education and Culture's guidelines in the selection system and exchange policies between regional clusters, although it faces challenges in the timeliness of implementation and distribution of Living Cost Assistance (BBH). The research results show that the Independent Student Exchange is effective and appropriate in increasing students' diversity orientation, reflected in the transformation of students' understanding and positive behavior towards diversity. The technical challenges encountered can be overcome through increasing coordination and improving the administration system to optimize the program.